1999
DOI: 10.1001/archderm.135.6.679
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Port-wine Stains With a Noncoherent Pulsed Light Source

Abstract: Objective: The flashlamp pulsed dye laser (FLPDL) is currently the treatment of choice for port-wine stains (PWS). We recently investigated whether a non-coherent intense pulsed light source (IPLS) would be effective in the therapy of PWS. Design and Patients:In order to evaluate the efficacy in treatment of PWS (especially adult-type dark and hypertrophic), a retrospective study of 37 patients (randomly selected) with a total of 40 PWS treated with IPLS was initiated. Clinical PWS characteristics recorded wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(86 citation statements)
references
References 45 publications
3
81
0
2
Order By: Relevance
“…Several alternative modalities, including intense pulse light and photodynamic therapy, have proven beneficial for treatment-resistant CMs, although a significant response or complete resolution is only seen in approximately 50% of patients for both modalities. [30][31][32][33] VENOUS MALFORMATIONS Venous malformations (VMs) are the most common vascular malformation, accounting for 44-64% of all vascular malformations. 34 They are classified according to the Hamburg classification 35 as truncular or extratruncular, with 40% of lesions localized to the extremities, 20% on the trunk and 40% on the head and neck.…”
Section: Capillary Malformationsmentioning
confidence: 99%
“…Several alternative modalities, including intense pulse light and photodynamic therapy, have proven beneficial for treatment-resistant CMs, although a significant response or complete resolution is only seen in approximately 50% of patients for both modalities. [30][31][32][33] VENOUS MALFORMATIONS Venous malformations (VMs) are the most common vascular malformation, accounting for 44-64% of all vascular malformations. 34 They are classified according to the Hamburg classification 35 as truncular or extratruncular, with 40% of lesions localized to the extremities, 20% on the trunk and 40% on the head and neck.…”
Section: Capillary Malformationsmentioning
confidence: 99%
“…These authors found that the investigated spectra provided homogeneous heating in the entire vessel that was sufficient for coagulating vessels > 60 mm. There is evidence in the literature for successful treatment of essential telangiectasias [30], rosacea [31,32], port-wine stains (PWS) [33][34][35][36][37], spider nevi [38], angiomas [39][40][41], and erythrosis [30]. For the treatment of essential telangiectasias, PWS, and rosacea level of evidence IIB is reached.…”
Section: Vascular Lesionsmentioning
confidence: 99%
“…While the treatment of leg telangiectasia was possible, additional advantages recognized early on was the IPL's ability as a specifi c modality to minimize the possibility of purpura common to pulsed dye lasers (PDL), as well as the elimination of hair and lentigines. Continued use proved that the device was of far greater utility for other indications than leg telangiectasias (Weiss et al 2000a ;Bitter 2000 ;Goldberg and Cutler 2000 ;Raulin et al 1999 ;Jay and Borek 1998;Weiss et al 1999 ;Raulin et al 1997b -d;Schroeter et al 1997 ) . The road to usability, reproducibility and effi cacy was a long one with some clinical users and many "laser experts" dismissing the IPL as a harmful and useless form of technology.…”
Section: Foreword Imentioning
confidence: 99%